Increased frequency (12%) of circulating chronic lymphocytic leukemia-like B-cell clones in healthy subjects using a highly sensitive multicolor flow cytometry approach - Nieto, Wendy G; Almeida, Julia; Romero, Alfonso; Teodosio, Cristina; López, Antonio; Henriques, Ana F; Sánchez, Maria Luz; Jara-Acevedo, María; Rasillo, Ana; González, Marcos; Fernández-Navarro, Paulino; Vega, Tomás; et al. (Blood, 2009)
Monoclonal B-cell lymphocytosis (MBL) indicates the presence of less than 5 x 10(9)/L circulating monoclonal B cells in otherwise healthy subjects. Recently, it has been reported that circulating chronic lymphocytic leukemia (CLL)-like B cells can be detected using 4- or 5-multicolor flow cytometry in 5% to 7% of adults with normal lymphocyte counts. We investigated the frequency of circulating monoclonal B cells in 608 healthy subjects older than 40 years with normal blood counts, using a highly sensitive 8-color flow cytometry approach and systematic screening for total PB leukocyte count higher than 5 x 10(6). We show that the frequency of PB monoclonal B cells is markedly higher than previously reported (12% for CLL-like B cells, found at frequencies of 0.17 +/- 0.13 x 10(9) cells/L), the incidence progressively increasing with age. Most cases (62%) showed clonal B-cell levels below the maximum sensitivity of the techniques described by others (< 0.01%), supporting the notion that detection of MBL may largely depend on the sensitivity of the flow cytometry approach used.